The concept of time in the novels of Sabiha Shubar - Sadkhan, Maryam; Abbas, Haider (Al-Adab Journal, 2023)
Time constitutes a fundamental pillar in the entire narrative structure of the novel, as it is the element chosen by the author to narrate facts, events and ideas, and then convey them to the reader through a narrator or a narrator, who may be an unknown entity, or a self-contained entity (such as the author’s personality) or A character appears and participates in the events of the story. Narrative texts that include the element of time lead to narrative paradoxes in the novel.